Let g(x)= 9*f(x) and let f1(-6) = -6

( LOOK ABOVE)The f1 part is the derivative

find g1 (-6)

Look above) The g1 part is the derivative

These are your answer choices

(a)-54

(b)zero

(c)-6

(d)9

Put which one you would put down, it will really help me out a lot

g'(x) =9 f'(x) =

g'(6) = 9 f'(6) = 9* (-6) =-54

Answer: option (a)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up